Implementasi Persamaan Kinematik Maju Pada Robot Manipulator - Herizon herizon; Ade Diana (Elektron : Jurnal Ilmiah, 2014)
Robot is one technology that is being developed at this time. Robot manipulators are widely used in industry, especially robotic arm that has a certain degree of freedom. The problems that occurred in the robot arm is the accuracy in determining the position of the object to be moved. This study aims to apply the method forward kinematics equation modeling on the movement of the robot manipulator in particular robot arm 3 degrees of freedom (DOF) equipped with a gripper which serves to clamp and move the object. The method used in this study is an experimental method in phases: the design of hardware and software, interconnect hardware and software in the system of movement of the robot. Joints actuator using servo motors. Manipulator control system is used to adjust the angular position of each joint with CodeVisionAVR programming language that is sent in parallel to the motor driver so as to produce pulses to move the bike. Forward kinematics equation modeling using trigonometric equations. Forward kinematics modeling applications on the movement of the robot arm that is used to provide information about the value of the angle and the coordinates of each joint. Results of testing the hardware controlled by software to show the error (error) the movement of each joint is varied by between 0.06% - 2.567%.